Pemikiran Fiqh Muhammad Wali Al-Khalidi - Nazaruddin Nazaruddin (Institut Agama Islam Negeri Palangka Raya, 2021)
Muhammad Wali Al-khalidi is a great scholar who is very well known in Aceh and Indonesia. There are many of his works in various disciplines, such as the fields of Sufism, Tawheed and fiqh. One of the interesting things about the work of Syeikh Muhammad Wali is that it is sociological empirically in which a theory is based on the phenomenon that develops in society. The purpose of this study is to examine the thoughts of Muhammad Wali Al-khalidi's fiqh, the nature of descriptive analysis research with the type of qualitative descriptive research with literature research, Abuya Muhammad Wali's fiqh thinking, namely the analytical method used on ijtihad based on the Koran and Hadith. This is the basic asset to achieve the criteria of a mujtahid, but because of the limitations of the majority of scholars today, it is impossible to get to the level of a mujtahid. Therefore, the solution taken by Abuya is to refer to the classical book texts compiled by previous scholars. Abuya Muhammad Wali's fatwa had a major influence, including the fatwa on death ceremony, where this fatwa refuted and straightened the fatwa of Abu Daud Beureueh which considered khanduri death to be heresy.